Espaço de lazer público: proposta projetual de espaço híbrido no bairro são Jorge - Mouas, Samia Yousseph (Brasil, 2022)
The crisis of public space as a result of changes in forms of consumption and the new model of urbanism where gated communities, shopping centers and similar spaces that are somehow tied to privatization, ends up making public spaces for use and social conviviality decadent, as they limit conditions and possibilities for the use of public space by its inhabitants, that is, urban environments, transformed into merchandise, are increasingly destined for exchange, which means that appropriation and modes of use tend to be subordinated (each increasingly) to the market. Given the above, the planning of policies for open space and its foundation on social inclusion, community cohesion, health and well-being, guide the preparation of this project. A project proposal is presented that results from the application of the concepts studied with the objective of promoting a public space of leisure with quality and safety, that intensifies the social relations of the place where it will be implanted and meets the needs of the users. From references that analyze and criticize the condition of "crisis" of the public space, this work proposes a hybrid experience "of leisure, quality and safety, which intensifies social relations" both for residents of the São Jorge neighborhood and any other group that feel invited to use the proposed object. Research and analysis converged to the guidelines of the work and from the deepening of the preliminary study, it is carried out as a project proposal presented.